STRESS DISTRIBUTION ON THE PERIODONTAL SUPPORT OF FIXED DENTAL PROSTHESIS WITH PIER ABUTMENT FINITE ELEMENT ANALYSIS - Ana Tufescu; Alice-Arina Ciocan Pendefunda; Antonela Beldiman; Oana Țănculescu; Raluca Baciu; Roxana Vasluianu; Maria Alexandra Mârțu; Nicoleta Ioanid (Romanian Society of Oral Rehabilitation, 2021)
Analysis of the occlusal stress distribution on the periodontal support of a 5‑unit intermediate abutment prosthesis with rigid connector it is still of real interest. Aim. Forces, with vertical directions, were applied simultaneously on the entire mandibular prosthesis having as intermediate pillar the second premolar, but also separately on each supporting tooth. Matherial and Methods. A three-dimensional rigid mandibular fixed prosthesis, retained on the canine (mesial pillar) and the second molar (distal pillar), with intermediate support on the second premolar, was simulated three-dimensionally (3D, soft - CATIA V15 R19). It was subjected to vertical stresses. The forces were applied continuously, simultaneously on the entire prosthesis and separately, for each supporting tooth. Results. In the case of vertical forces, the highest concentration of stress was observed in the canine, the most distal pillar. Conclusions. In clinical situations where the fixed prosthesis with rigid connectors includes intermediate teeth, occlusal balancing, especially is essential for the perenity of the restoration.